2011 Seventh International Conference on Natural Computation 2011
DOI: 10.1109/icnc.2011.6022512
|View full text |Cite
|
Sign up to set email alerts
|

A robust smear removal method for inter-frame Charge-Coupled Device star images

Abstract: In order to eliminate the influence of Smear Effect on follow-up processing of star images, this paper researched the source and statistical model of Smear Effect. After researching the working progress of inter-line Charge Coupled Device(CCD), inter-frame CCD and full-frame CCD, this paper builds a statistical model for the background noise and then proposes an algorithm to do radiometric correction in smear images based on modeling and estimating the intensity of background noise in star image. Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…12, the TopHat algorithm and the Spread TopHat algorithm in Ref. 13, and the method proposed in this paper. It is assumed that the length of the structure elements of TopHat and Spread TopHat is 25 pixels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…12, the TopHat algorithm and the Spread TopHat algorithm in Ref. 13, and the method proposed in this paper. It is assumed that the length of the structure elements of TopHat and Spread TopHat is 25 pixels.…”
Section: Resultsmentioning
confidence: 99%
“…In response to the smear problem, related works have been developed focusing on three topics: removing fake targets in the smeared image after detection, 6 employing special hardware 7 or modifying the design of CCD image sensors, 8 , 9 and numeric algorithms for postfacto correction of image smear 10 19 Generally, the latter is considered the most economical and efficient solution. For instance, Huang et al 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first of these assumptions was investigated by Knox [8], who showed that smearing can be used in specific cases to recover the values of saturated pixels in the image. More recently, different smearing correction techniques have been developed that are optimal for specific imaging applications [9,10] or used for real time correction [11].…”
Section: Introductionmentioning
confidence: 99%